Shaping the esp curriculum of an english for PhD students program: a colombian case study of questionnaire research - Janssen, Gerriet; Nausa, Ricardo; Rico, Carlos (Colombian Applied Linguistics Journal, 2012)
This report presents the findings from an EAP curriculum development project directed towards PhD students at Colombian university. An analysis of this stakeholder group’s learning needs was conducted through questionnaire research, focusing on (a) describing students’ situated contexts and interests and (b) obtaining data contributing towards future program development. Measures of central tendency, dispersion, and internal consistency for each section of the questionnaire are reported. Key results include these students’ strong interest in EAP programming, their language needs and experience regarding their intellectual production, and their perceived importance of different language sub-skills in both the local and international contexts. The results highlight the importance of continued evaluation cycles and the important role EAP coursework has for PhD students today.